Cities and Entrepreneurs over Time: Like a Horse and Carriage? - Wim Naudé (Institute of Labor Economics (IZA), 2017)
Entrepreneurship, being largely an urban phenomenon, co-evolves over time with cities. While this relationship is like a 'horse and carriage', it is not a straightforward one, more akin to 'love and marriage'. In this paper I explore the co-evolution of entrepreneurship and cities. First, I provide a stylized model of development wherein the rise of cities (urbanisation) is the outcome of the activities of entrepreneurs. Second, I provide a stylized overview of entrepreneurship and cities from earlier to later stages of development. In young cities a challenge for establishing an entrepreneurial ecosystem is the provision of infrastructure for business' connectivity and energy. Good urban planning and management skills, including urban policing and dealing with land disputes, may be amongst the most sorely needed in the emerging world today. At more intermediate and later stages of development, cities can become entrepreneurial hotspots and even 'global startup cities'. Three main challenges during these stages, as far as the role of entrepreneurs are concerned, relates to (i) rising property prices and rents, urban congestion and fierce business competition, (ii) environmental sustainability and (iii) the impacts of technology that could make centralization in cities for business purposes unnecessary. Entrepreneurs have important roles to play as property developers and in the creation of new business models and new markets. They can be the drivers of 'smart' cities, 'circular' cities, and of sub-urbanisation and secondary city growth. Over time not all cities, and their entrepreneurs, will necessarily continue to grow and prosper. There is nothing inevitable in the rise of any particular city and the prosperity of its entrepreneurs. Cities do not only generate, they also degenerate. I conclude that the heterogeneity, serendipity and context-specificity of global urbanisation implies that there is much that is still unknown about the specifics of the relationship between cities and its entrepreneurs over time.
Keywords: L26; L53; M13; O18; R10; 330; entrepreneurship; urbanisation; development